THE SOCIAL-ECONOMIC NATURE OF THE LABOR MARKET AND THE CONCEPT OF INCLUSION (Scientific electronic journal "Labor Economics and Human Capital", 2023)
In this article, the socio-economic nature of the concepts of “labor market” and “inclusive labor market” is widely covered and the definition of the concept of "inclusive labor market" is elaborated. Participation of persons with disabilities in the labor market, benefits in employment practices, recruitment are covered.
Keywords: persons with disabilities, inclusion, labor market, employment.